2019
DOI: 10.14302/issn.2694-2275.jzr-19-2695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Levels of Spirulina (Arthropsira platensis) on Feed Intake and in vivo Digestibility of Trypsacum laxum in Guinea Pig (Cavia Porcellus L)

Abstract: The intake and in vivo digestibility of Trypsacumlaxum in guinea pigs according to the graded level of spirulina was evaluated in Cameroon. 20 animals aged of 6 months with an average weight of 450 ± 50 g were randomly divided into 4 equivalent groups. Each group received T. laxum and 40g of compound feed containing 0% (TS0), 2% (TS2), 4% (TS4), and 6% (TS6) of spirulina. Feed intake was the different between the left over and the quantity served. The sample of T. laxum and those of each diet as well as feces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This behavior has not been reported in other literature for laying hens, however, as mentioned before, there are no other trials with such a high level of inclusion as 6%, as in the present study. Nguedia et al (2019) reported a decrease of 6.13 g/animal/day in dry matter intake for guinea pigs supplemented with 6% Arthrospira maxima compared to supplementation at 4%. However, the lower feed intake did not result in a change in feed conversion ratio (FCR).…”
Section: Effect Of Inclusion Of Arthrospira Maxima Microalgae In Layi...mentioning
confidence: 99%
“…This behavior has not been reported in other literature for laying hens, however, as mentioned before, there are no other trials with such a high level of inclusion as 6%, as in the present study. Nguedia et al (2019) reported a decrease of 6.13 g/animal/day in dry matter intake for guinea pigs supplemented with 6% Arthrospira maxima compared to supplementation at 4%. However, the lower feed intake did not result in a change in feed conversion ratio (FCR).…”
Section: Effect Of Inclusion Of Arthrospira Maxima Microalgae In Layi...mentioning
confidence: 99%
“…Cavy farming is widely practiced in Cameroon, especially in low-income families where it constitutes an important source of protein (Noumbissi et al, 2014). In village farming, these animals feed on kitchen waste and harvest residues, which o en have de ciencies in essential nutrients, resulting in low production and early mortality (Nguedia et al, 2019). However, its optimal utilization as a protein source requires e cient feeding to improve productivity (Zougou et al, 2017).…”
Section: Introductionmentioning
confidence: 99%